On the Idea that God is Continuously Re-creating the Universe - Pavelich, Andrew (Sophia, 2007)
Many theists believe that God is continuously acting to sustain the universe in existence. One way of understanding this act of sustenance is to see God as actually creating the universe anew at each moment. This paper argues against the coherence of this view by drawing out some of its consequences. I argue that the re-creationist must deny the causal efficacy of created f things, as well as the identity of things across time. Most problematically, I argue that re-creationism ultimately denies the reality of time itself.